Learning the language of dentistry : disciplinary corpora in the teaching of English for specific academic purposes - Crosthwaite, Peter; Cheung, Lisa Mei Ling (Studies in corpus linguistics., 2019)
This book explores the affordances of disciplinary corpora for the teaching and learning of the 'language of dentistry', within the field of English for Specific Academic Purposes (ESAP). We extract disciplinary register features and vocabulary from three key genres of the dentistry discipline (published experimental research articles, case reports, and novice / professional research reports within the Dental Public Health domain), before integrating these features into ESAP pedagogy in the form of corpus-based ESAP materials that promote student-led direct engagement with disciplinary corpora - an approach known as 'data-driven learning'. This book is an addition to the field of corpus linguistics and ESAP, and is especially targeted at ESAP professionals who are required to teach disciplinary discourses but who may struggle to know what to teach as non-experts of the target discipline.